Early Loss of Pericytes and Perivascular Stromal Cell-Induced Scar Formation after Stroke. Issue 3 (March 2013) - Fernández-Klett, Francisco; Potas, Jason R; Hilpert, Diana; Blazej, Katja; Radke, Josefine; Huck, Jojanneke; Engel, Odilo; Stenzel, Werner; Genové, Guillem; Priller, Josef
Despite its limited regenerative capacity, the central nervous system (CNS) shares more repair mechanisms with peripheral tissues than previously recognized. Scar formation is a ubiquitous healing mechanism aimed at patching tissue defects via the generation of fibrous extracellular matrix (ECM). This process, orchestrated by stromal cells, can unfavorably affect the capacity of tissues to restore function. Vascular mural cells have been found to contribute to scarring after spinal cord injury. In the case of stroke, little is known about the responses of pericytes (PCs) and stromal cells. Here, we show that capillary PCs are rapidly lost after cerebral ischemia in both experimental and human stroke. Coincident with this loss is a massive proliferation of resident platelet-derived growth factor receptor beta (PDGFRβ) + and CD105 + stromal cells, which originate from the neurovascular unit and deposit ECM in the ischemic mouse brain. The presence of PDGFRβ + stromal cells demarcates a fibrotic, contracted, and macrophage-laden lesion core from the rim of hypertrophic astroglia in both experimental and human stroke. We suggest that a previously unrecognized population of CNS-resident stromal cells drives a dynamic process of scarring after cerebral ischemia, which appears distinct from the glial scar and represents a novel target for regenerative stroke therapies.